Influence of Managing School Feeding Programme on Universal Basic Education in South-West Geo-Political Zone, Nigeria - AFOLABI, Kafilat Adeola; MAINAM, B. A.; HOWUMI, A. A. (International Journal of Educational Management, 2025)
The study examined the influence of managing school feeding program on Universal Basic Education in the South-West geopolitical zone of Nigeria. The study's objectives include, among others, assessing the influence of planning a school feeding program on Universal Basic Education in the south-West geopolitical zone of Nigeria. The study adopted a descriptive survey research design. The population comprised8,242 head teachers, 63,200 Teachers, and 12,472 vendors and cooks in Basic Schools of South-West Zone, Nigeria, making a total of 83,917. A Multi-stage sampling procedure was employed to select the sample for the study. The study adopted the KENPRO (2013) sampling size table to select 384 respondents. A structured questionnaire comprising 60 statements on a five-point Likert rating scale validated by experts with reliability coefficients of 0.69 and 0.81 was administered to the respondents. The statistical tools used for data analysis include simple percentages, the mean, the standard deviation, and One-way Analysis of Variance (ANOVA). The findings of the study revealed that planning school feeding programs did not influence universal basic education in the south-west geo-political zone of Nigeria with a P value of 0.119, which is greater than the 0.05 level of significance, and Organizing school feeding programs have tremendously influenced universal basic education in the south-west geo-political zone of Nigeria with a P value of 0.005, which is less than the 0.05 level of significance, amongst others. The study concluded that managing school feeding programs has influence universal basic education in the south-west geo-political zone of Nigeria. The study recommended the effective coordination of School feeding programs should be a mechanism to encourage good behavior